2021
DOI: 10.1093/ckj/sfab008
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes after kidney transplantation, let’s focus on the patients’ perspectives

Abstract: Graft function and patient survival are traditionally the most used parameters to assess the objective benefits of kidney transplantation. Monitoring graft function, along with therapeutic drug concentrations and transplant complications, comprise the essence of outpatient management in kidney transplant recipients (KTRs). However, the patient’s perspective is not always included in this process. Patients’ perspectives on their health after kidney transplantation, albeit subjective, are increasingly acknowledg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 68 publications
0
12
0
2
Order By: Relevance
“…A common and often neglected issue, posttransplant symptom burden has a negative impact on KT recipients’ ability to participate in physical and social activities of daily life (Ju et al, 2019). Multiple factors contribute to high symptom burden in KT recipients, including residual kidney dysfunction, comorbid conditions (e.g., diabetes and hypertension), and side-effects induced by immunosuppression (Sullivan et al, 2020; Wang et al, 2021). Furthermore, health care providers’ limited awareness of the negative effects of symptom burden after KT poses a major challenge to developing care improvement strategies for the posttransplant period.…”
mentioning
confidence: 99%
“…A common and often neglected issue, posttransplant symptom burden has a negative impact on KT recipients’ ability to participate in physical and social activities of daily life (Ju et al, 2019). Multiple factors contribute to high symptom burden in KT recipients, including residual kidney dysfunction, comorbid conditions (e.g., diabetes and hypertension), and side-effects induced by immunosuppression (Sullivan et al, 2020; Wang et al, 2021). Furthermore, health care providers’ limited awareness of the negative effects of symptom burden after KT poses a major challenge to developing care improvement strategies for the posttransplant period.…”
mentioning
confidence: 99%
“…To the best of our knowledge, this study is the first one to report a positive impact of therapeutic education on transplant patients’ health‐related quality‐of‐life. HR‐QOL is a major outcome from the patient’s standpoint and is increasingly acknowledged as such by healthcare providers [29]. The mean mental and physical HR‐QOL scores at one year were overall higher in patients in the therapeutic education group.…”
Section: Discussionmentioning
confidence: 99%
“…It is demonstrated that KT provides superior life expectancy [61][62][63] and QoL [64][65][66] than dialysis. Nonetheless, returning to dialysis after a failed transplant entails a greater risk of death than starting RRT for the first time [11,40,43,67,68].…”
Section: Post-transplant Recipient and Allograft Survivalsmentioning
confidence: 99%